Pain Neuroscience with exercise versus Biomedical Education with Exercise for treatment of Rotator Cuff-related Shoulder Pain: A Randomised Clinical Trial - Sidhant Silan; Bhawna Verma; Umesh Yadav; Kusum Yadav (Journal of Clinical and Diagnostic Research)
Introduction: A common clinical issue, rotator cuff pathology has a worldwide prevalence of 20.7%. It has been noted that exercise has traditionally been a primary treatment approach for shoulder disorders, but more recently, Pain Neuroscience Education (PNE) and Biomedical Education (BME) programs have shown promising effects in decreasing patients’ pain and disability. Aim: To compare the efficacy of pain neuroscience and BME programs with exercise in individuals with rotator cuff-related pain. Materials and Methods: A concurrent parallel randomised group clinical study was conducted at the College of Physiotherapy, Pandit Bhagwat Dayal Sharma University of Health Sciences, Rohtak, Haryana, India from August 2022 to August 2023. 100 patients who were randomly assigned to two groups: 50 in the PNE plus exercise group and 50 in the BME plus exercise group. The study’s outcome measures included pain intensity (measured by the Numeric Pain Rating Scale, NPRS), shoulder disability (assessed using the Shoulder Pain and Disability Index, SPADI), kinesiophobia (measured by the Tampa Scale), and pain experience (assessed using the Pain Catastrophising Scale, PCS). Data were collected at baseline, two weeks, and four weeks for all variables. Between-group comparisons were performed using independent samples t-tests. Results: The mean age of participants in the PNE plus exercise group was 47.24±12.61 years, while in the BME plus exercise group, it was 45.46±11.87 years. In the PNE plus exercise group, there were 36 males and 14 females, whereas in the BME plus exercise group, there were 34 males and 16 females. A total of 30 females and 70 males participated in the study. At the 2nd and 4th weeks, there were statistically significant differences between the PNE and BME groups regarding kinesiophobia and pain-related beliefs (p≤0.05). However, there were no statistically significant differences between the two groups concerning pain intensity and shoulder disability (p>0.05). Conclusion: The study demonstrated that the PNE program, when coupled with exercise, was more effective in reducing kinesiophobia and altering perceptions about pain. This information, which emphasises the potential benefits of incorporating PNE into treatment regimens for patients with rotator cuff-related pain, is valuable for healthcare providers.